2022
DOI: 10.3389/fmats.2022.837289
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Study of the Static and Fatigue Performance of Flax, Glass, and Flax/Glass Hybrid Composites on the Structural Example of a Light Railway Axle Tie

Abstract: The most common studies in the literature are those analyzing fatigue life under cyclic loading for flax fiber-reinforced composites. A novel type of staple fiber yarn made from flax tow with almost unidirectional fiber orientation and a quasi-unidirectional fabric was developed for composite applications. Additionally, a hybrid material made of flax and glass was produced for a demonstrator component (an axle tie of a narrow-gauge railway). For such an application, the investigation of fatigue strength is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…A combination of bast and carbon fibres can lead to an increase in the stiffness and toughness of pure bast fibre-reinforced composites and, at the same time, significantly improve the damping properties of pure carbon fibre-reinforced composites [ 63 , 64 , 65 , 66 ]. It has also been shown that the fatigue strength of, e.g., flax fibre-reinforced materials is better than that of glass fibre-reinforced composites above a certain number of loading cycles [ 67 ]. However, other cellulose-based fibres can also be combined, e.g., bast and regenerated cellulose fibres, to increase the toughness of the bast fibre-reinforced composites [ 45 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…A combination of bast and carbon fibres can lead to an increase in the stiffness and toughness of pure bast fibre-reinforced composites and, at the same time, significantly improve the damping properties of pure carbon fibre-reinforced composites [ 63 , 64 , 65 , 66 ]. It has also been shown that the fatigue strength of, e.g., flax fibre-reinforced materials is better than that of glass fibre-reinforced composites above a certain number of loading cycles [ 67 ]. However, other cellulose-based fibres can also be combined, e.g., bast and regenerated cellulose fibres, to increase the toughness of the bast fibre-reinforced composites [ 45 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Graupner et al [108] compared the static and fatigue performance of different flax, glass, and flax/glass-reinforced composites using an epoxy matrix manufactured by resin transfer molding (RTM). The results showed that at high loading cycles, from about 7 3 to 8 3 , high-quality flax samples had higher fatigue strength than glass samples, showing the potential durability of flax composites with processing optimization.…”
Section: Durability and Fatigue Of Nfrp Compositesmentioning
confidence: 99%
“…For now, the improvement of fatigue performance of PFCs has not gained as much attention as other aspects of PFCs. Nonetheless, recent available research work has revealed a general trend that good fiber/matrix adhesion can lead to higher long-term durability [86,87]. Asumani and Paskaramoorthy [88] performed two fiber treatments (alkali-alone treatment and combined alkali-silane treatment) on kenaf fibers and tested the fatigue performance of kenaf-reinforced polypropylene composites.…”
Section: Towards Improving Fatiguementioning
confidence: 99%